A literature review on english communication skills among accounting undergraduates - Faridah Musa,; Melor Md Yunus,; Zarina Othman, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Being proficient in English and having good communication skills have been recognized as important criteria employers look for in hiring fresh graduates. This review paper aims to present the relevant literature on English communication skills of accounting undergraduates in Malaysia from the perspectives of both the undergraduates and the employers. It also examines suggestions for helping undergraduates improve their English communication skills. This review covered the related literature published in the past ten years from the year 2010 until 2020 using research search engines, namely Google Scholar and Research Gate. It was found that most studies on English communication skills in Malaysia involved undergraduates from several fields of study such as engineering, computer science, hospitality, business and marketing, but very few on accounting undergraduates. Thus, there exists a gap in the literature related to the present study on the English communication skills of undergraduates from this field. Furthermore, a large number of the past studies were found to employ the quantitative method of data collection such as through questionnaires and surveys, while studies employing the qualitative method were less frequent. The implication based on the findings of this review paper is the need for more in-depth studies to further explore the English communication skills of accounting undergraduates in Malaysia.